Optimization Process of the Pepsin-Solubilized Collagen from Lizardfish (Saurida tumbil Bloch, 1795) Skins by-Product - Jaziri, Abdul Aziz; Shapawi, Rossita; Mohd Mokhtar, Ruzaidi Azli; Md. Noordin, Wan Norhana; Zulfigar, Siti Balqis; Nurul, Huda (Indonesian Food Science and Technology Journal, 2023)
By-products from the marine fish processing are rich in organic compounds that can be converted into value-added products like collagen, and it is thought as an ideal candidate polymer for such research and medical applications. The lizardfish (Saurida tumbil Bloch, 1795) skin collagen had been investigated by our previous work, but an effective extraction method is needed to increase the yield of collagen. The purpose of this study was to optimize the method used to extract pepsin-solubilized collagen (PSC) from lizardfish skin. We employed an approach of one factor at a time (OFAT), along with response surface methodology (RSM) utilizing a central composite design (CCD), to attain the highest possible yield of the extracted collagen. Additionally, its properties were also assessed comparatively. The suggested optimal conditions for extraction were a pepsin concentration of 1.87%, a liquid-solid ratio of 24.90 mL/g, and a hydrolysis period of 38.09 h. Using these conditions resulted in a PSC yield of 21.82 g/100g, which closely matched the predicted collagen value.